Spoof Surface Plasmon Polaritons Antenna - Geng, Junping; Ren, Chaofan; Wang, Kun.; Zhou, Han.; Zhang, Jing.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book investigates in detail some new spoof surface plasmon polaritons (SSPPs) structures and their applications to antenna. It introduces the working principle and radiation characteristics of directional antenna, omnidirectional antenna, reconfigurable antenna and phase-mode antenna based on SSPPs structure. Especially, the irregular SSPPs structure, such as T-shaped and m-shaped SSPPs structures, is introduced to low-profile end-fire antenna with vertical polarization; the rotated SSPPs structure is applied to CP end-fire antenna and omnidirectional antenna; PIN circuit combining with SSPPs structure is used to pattern reconfigurable antenna; the novel phase-mode SSPPs antennas with multi-modes are performed too. This book proposes a continuous method to develop the potentialities of the SSPPs antenna. And the readers can study the method or ideas of the SSPPs antenna, even graft the methods to other SSPPs antenna. The book is intended for undergraduate and graduate students who are interested in SSPPs antenna technology, researchers investigating high-performance antenna, and antenna design engineers working on multi-function antenna applications.
Introduction -- Basic Principles of Spoof Surface Plasmon Polaritons -- Multipole Antenna Based on Spoof Surface Plasmon Polaritons Structure -- Endfire Antenna Based on Spoof Surface Plasmon Polaritons -- Low Frequency Omnidirectional Antenna Based on Spoof Surface Plasmon Polaritons -- Study on the Rotated Spoof Surface Plasmon Polaritons Structure -- Iregular Shaped Spoof Surface Plasmon Polaritons Antenna -- Pattern reconfigurable antenna based on Spoof Surface Plasmon Polaritons -- Phased-mode Spoof Surface Plasmon Polaritons Antenna 169.
Keywords: Telecommunication; Electronic circuits; Wireless communication systems; Mobile communication systems; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems; Wireless and Mobile Communication; Antennas (Electronics) -- Technological innovations